Complete mitochondrial genome of the Saker falcon, Falco cherrug (Falco, Falconidae). (2nd September 2016) - Lu, Jing; Lu, Jiang; Li, Xiang-Feng; Jiang, Hui
Abstract: The Falco cherrug (Saker falcon) is a large bird of prey. In this article, the complete mitochondrial genome of F. cherrug has been determined for the first time. The mitogenome (18, 059 bp) comprised 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes and 1 control region. Most protein-coding genes started with an ATG or ATA codon except for COI, which initiated with nontypical start codon of GTG instead, and terminated with the typical stop codon (TAA/TAG/AGA/AGG) or a single T. Two tandem repeats were identified in the control region, which was almost identical to Falco peregrinus, and the length of these two repeats are 204 bp and 291 bp, respectively.